Enhancing visual perception by modulating prestimulus alpha and beta power with tRNS - Jinwen Wei; Huiru Zou; Qianyuan Tang; Ziqing Yao; Gan Huang; Zhen Liang; Li Zhang; Lijie Ren; Xiaodong Cai; Chen Yao; Changsong Zhou; Zhiguo Zhang (Communications Biology)
Abstract Visual variability is linked to prestimulus alpha (8–13 Hz) and beta (13–30 Hz) power fluctuations, yet their causal role remains unclear. Using transcranial random noise stimulation (tRNS), we tested whether externally modulating cortical excitability could influence these oscillations and alter perception. In a sham-controlled, within-subject design, 29 participants completed a visual detection task combined with electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) recordings. Mental fatigue was modelled as a state-dependent factor. tRNS, primarily under low fatigue, increased online oxyhemoglobin (HbO) amplitude, suppressed offline prestimulus alpha and beta power, and reduced offline visual contrast threshold (VCT), indicating enhanced perception. Further analyses revealed that fatigue influenced the oscillations’ responsiveness to tRNS, and that under low fatigue, alpha power, more than beta, demonstrated greater functional sensitivity to VCT. These findings demonstrate that tRNS can improve perception by modulating alpha/beta oscillations in specific brain states, highlighting the role of brain state in neuromodulation efficacy.